Spontaneous Pneumothorax in a Patient with Systemic Lupus Erythematosus and Recent Infection with Coronavirus. (22nd August 2022) - Graves, Nicholas; Flint, Julia; Sagdeo, Amol; Askari, Ayman; Ball, Patrick; Morrissey, Hana
Abstract : A 50-year-old woman with a history of systemic lupus erythematosus and a recent infection with COVID-19 presented to the emergency department with acute shortness of breath twice in 10 days. She was diagnosed with myopericarditis attributed to COVID-19 infection (first admission), and chest X-ray revealed a small left-sided pneumothorax, pericardial effusion (second admission), with no mediastinal shift or other signs of tension. Computed tomography confirmed these results and revealed a few small cysts in the right lung. An echocardiogram demonstrated normal heart anatomy and filling dynamics. The patient was diagnosed with simple pneumothorax and ongoing myopericarditis managed with colchicine, ibuprofen, and low-dose prednisolone. The patient responded to treatment and was discharged. Pneumothorax association with COVID-19 is reported in a small number of publications, but the association is less clear with SLE. Our patient may have been predisposed to developing pneumothorax after COVID-19 infection due to her existing connective tissue disorder.